Proceedings of the Fifteenth ACM Conference on Economics and Computation 2014
DOI: 10.1145/2600057.2602836
|View full text |Cite
|
Sign up to set email alerts
|

Optimal impartial selection

Abstract: We study the problem of selecting a member of a set of agents based on impartial nominations by agents from that set. The problem was studied previously by Alon et al. and by Holzman and Moulin and has important applications in situations where representatives are selected from within a group or where publishing or funding decisions are made based on a process of peer review. Our main result concerns a randomized mechanism that in expectation selects an agent with at least half the maximum number of nomination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…Given the set of submitted papers and reviewers, this graph is fixed and cannot be controlled. Note that the conflict graph C defined above can be viewed as a generalization of the authorship graph in the previously-studied settings (Merrifield and Saari, 2009;Alon et al, 2011;Holzman and Moulin, 2013;Fischer and Klimm, 2015;Kurokawa et al, 2015;Aziz et al, 2016;Kahng et al, 2017) of peer grading and grant proposal review, where each reviewer (paper) is connected to at most one paper (reviewer).…”
Section: Problem Settingmentioning
confidence: 99%
“…Given the set of submitted papers and reviewers, this graph is fixed and cannot be controlled. Note that the conflict graph C defined above can be viewed as a generalization of the authorship graph in the previously-studied settings (Merrifield and Saari, 2009;Alon et al, 2011;Holzman and Moulin, 2013;Fischer and Klimm, 2015;Kurokawa et al, 2015;Aziz et al, 2016;Kahng et al, 2017) of peer grading and grant proposal review, where each reviewer (paper) is connected to at most one paper (reviewer).…”
Section: Problem Settingmentioning
confidence: 99%
“…According to their definition, an impartial selection rule should have as low approximation ratio as possible. This line of research was concluded by the work of Fischer and Klimm [10] who proposed impartial mechanisms with the optimal approximation ratio of 2.…”
Section: Introductionmentioning
confidence: 96%
“…In distributed multi-agent systems, leader election (e.g., see [2]) can be thought of as a selection problem of similar flavor. Other notable examples include the selection of a representative in a group [10], funding decisions based on peer reviewing [10] or even finding the most popular user of a social network [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is extremely unnatural and relies on the fact that every vertex bar one abstains from voting. Indeed, Fisher and Klimm [4] showed that without abstentions the permutation mechanism is at least 7 12 -optimal. They leave open the possibility that the permutation mechanism actually proffers a better approximation guarantee than 7 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This impartial selection problem was introduced independently by Holzman and Moulin [5] and Alon et al [1]. Fisher and Klimm [4] showed that the permutation mechanism is impartial and 1 2 -optimal, that is, it selects an agent who gains, in expectation, at least half the number of votes of most popular agent. Furthermore, they showed the mechanism is 7 12 -optimal if agents cannot abstain in the election.…”
mentioning
confidence: 99%